The usefulness of using Dikir Barat in Mandarin learning / Goh Ying Soon...[et al.] - Goh, Ying Soon; Lee, Chai Chuen; Ngo, Kea Leng (Universiti Teknologi MARA, Kedah, 2016)
This paper aims to shed some light on the usefulness of using Dikir Barat in Mandarin in supporting Mandarin learning among the non-native Chinese learners. Song can be a very useful tool to enhance learning Mandarin motivation among learners. This study was carried out during a Dikir Barat in Mandarin competition held at UiTM (Kedah). A self-developed questionnaire was distributed to gain understanding on the view of the participants on the usefulness in using Dikir Barat in Mandarin to support Chinese learning among these non-native Chinese learners. Descriptive and inferential statistics were used to analyze the gathered data. It was found that students agreed that Dikir Barat in Mandarin is useful to enhance their learning motivation. Thus, activity such as Dikir Barat in Mandarin can be used as creative practice in teaching Mandarin as a foreign language in specific and also for other foreign languages.